Persistent olfactory complaints after COVID-19: a new interpretation of the psychophysical olfactory scores - Clair Vandersteen; Magali Payne; Louise-Émilie Dumas; Victoria Metelkina-Fernandez; Alexandra Plonka; David Chirio; Élisa Demonchy; Karine Risso; Florence Askenazy-Gittard; Nicolas Guevara; Laurent Castillo; Valeria Manera; et al. (Rhinology Online, 2021)
Background: Sudden olfactory loss is a major symptom of SARS-CoV-2 infection and has a negative impact on daily life quality. Almost 80% of disorders regress spontaneously. No precise characterization of the medium- and long-term olfactory symptoms has been carried out yet, apart from self-assessments. The main objective of this work was to characterize persistent smell disorders in this population. Methodology: Consecutive patients consulting to the ENT department with post-Covid19 olfactory loss were included. The clinical examination included an analog scale for the self-assessment of olfactory recovery), a nasofibroscopy, the Sniffin’ Stick Test and the short version of the Questionnaire of olfactory disorders. Results: Among the 34 patients included, based on the Sniffin’ Sticks Test, 29.4% (n=10) could be classified as normosmic, 55.9% (n=19) as hyposmic and 14.7% (n=5) as functional anosmic). Only olfactory identification impairment was significantly correlated with olfactory complaint and daily anxiety and annoyance related to lack of olfaction recovery. This identification disorder seemed to worsen over time. Conclusions: It is crucial to assess odor identification disorders in case of persistent olfactory complaints after COVID-19. It is fundamental to target this disorder, as it does not improve spontaneously and negatively impact quality of life.